A review of the neural basis underlying the acoustic startle response with a focus on recent developments in mammals. (May 2023) - Zheng, Alice; Schmid, Susanne
Abstract: The startle response consists of whole-body muscle contractions, eye-blink, accelerated heart rate, and freezing in response to a strong, sudden stimulus. It is evolutionarily preserved and can be observed in any animal that can perceive sensory signals, indicating the important protective function of startle. Startle response measurements and its alterations have become a valuable tool for exploring sensorimotor processes and sensory gating, especially in the context of pathologies of psychiatric disorders. The last reviews on the neural substrates underlying acoustic startle were published around 20 years ago. Advancements in methods and techniques have since allowed new insights into acoustic startle mechanisms. This review is focused on the neural circuitry that drives the primary acoustic startle response in mammals. However, there have also been very successful efforts to identify the acoustic startle pathway in other vertebrates and invertebrates in the past decades, so at the end we briefly summarize these studies and comment on the similarities and differences between species. Highlights: Startle is a useful clinical and experimental tool for studying sensory filtering and gating. Neural mechanisms underlying startle are highly conserved. Novel approaches have further elucidated neural mechanisms of startle. Differences and similarities between species are discussed.